Topical Catharanthus roseus gel modulates TNF-α expression and SOD activity in UVB-induced skin: an in vivo experimental study - Noviana Gunawan, Gina; Trisnadi, Setyo; Sarosa , Hadi (Universitas Muhammadiyah Purwokerto, 2026)
Background: Subchronic UVB exposure induces oxidative stress and skin inflammation, characterized by increased TNF-α expression and decreased antioxidant activity, including superoxide dismutase (SOD). Catharanthus roseus contains bioactive compounds with potential anti-inflammatory and antioxidant properties; however, evidence regarding its topical effects on UVB-induced skin damage remains limited. Objective: To evaluate the effects of Catharanthus roseus extract gel on TNF-α expression and SOD activity in UVB-induced skin and to compare the effectiveness of 15% and 30% concentrations. Methods: A post-test-only controlled experimental study was conducted using 30 mice divided into five groups: normal control, negative control, positive control (vitamin E), 15% extract gel, and 30% extract gel. TNF-α expression and SOD activity were measured using ELISA and analyzed with one-way ANOVA. Results: UVB exposure significantly increased TNF-α expression and decreased SOD activity in the negative control group compared with the normal group. Treatment with Catharanthus roseus extract gel improved both parameters. No significant differences were observed between the 15% and 30% concentrations for TNF-α (p = 0.376) or SOD activity (p = 0.237), indicating comparable effects. Conclusions: Topical Catharanthus roseus extract gel modulates TNF-α expression and SOD activity in UVB-induced skin. Comparable effects between 15% and 30% concentrations suggest that the lower concentration may be sufficient to achieve the desired biological response.